The Role of Quantitative Easing on the Stability of Financial Markets in Iran - Seyed Majid Rasolpour Arabi; Ahmad Jafari Samimi; Amir Mansour Tehranchian; Majid Aghaei (International Journal of Business and Development Studies, 2024)
In the present study, the role of quantitative easing on the stability of financial markets in Iran has been analyzed from the quarterly data of 2006-2021 using the econometric model with vector error correction model (VECM). To estimate the model from some observable variables, the effects of quantitative easing on financial market variables, including (liquidity volume, capital adequacy rate, credits granted to the private sector by banks, bank deposit interest rate, stock market index and exchange rate) were estimated. The data was extracted from the official website of the Securities and Exchange Organization and the Central Bank. In VECM models, the estimation was done in both short-term and long-term periods with the aid of Eviews software. The findings of the research, based on the estimation of long-term and short-term relationships, show that quantitative easing has a positive and significant effect on the stability of financial markets. With the MP1 index increasing by one percent, the Financial Market Stability Index increased by 4.157 percent.